COVID-19: A New Horizon in Congenital Heart Diseases - Aghaei Moghadam, Ehsan; Mohammadzadeh, Shabnam; Sattarzadeh Badkoubeh, Roya; Ghamari, Azin; Rabbani, Ali; Mohebbi, Ali; Zeinaloo, Aliakbar; Ashrafi, Mahmoudreza; Kamran, Niyoosha; Masoominasab, Paniz; Mahmoudi, Zahra; Zamani Mehryan, Asma; et al. (Frontiers in Pediatrics, 2021)
Objective: Previous studies have demonstrated that Both Children and adult patients with a history of congenital heart disease (CHD) are high risk for COVID19 infection. This study investigates the status of COVID 19 infection among children undergoing surgical repair within the past two years. Methods: All alive patients operated in a tertiary referral center between March 2018 and March 2020 were recruited in the present study. Detailed demographic, past medical, and surgical history and physical examination were reviewed for each patient. During the COVID19 pandemic, data regarding the patients' status was collected by telephone survey from April 15th to April 30th, 2020. Results: Total number of 210 patients are analyzed in this study. All participants’ median age was 21.59 months (IQR= 12-54.67), and 125(59.5%) were female. The median interval between surgery and COVID19 assessment was 305 days (IQR= 215-400). 67 (32%) patients used ARB/ACE inhibitor (Spironolactone and/or Captopril). Sixteen patients (7.6%) were symptomatic and had positive chest CT results and/or RT-PCR Compared to the previously reported prevalence of COVID19 among the pediatric population (2.4% of children with less than 18 years of age), the prevalence of COVID19 among the patients operated due to CHD in the present study was significantly higher (P=0.00012). Two patients were admitted to the intensive-care unit (ICU); one patient was discharged two weeks later with acceptable status, and one patient died two days after ICU admission due to cardiac and respiratory arrest and myocarditis. The complexity of the underlying cardiac disorders was not different between patients with low risk (P= 0.522), suspicious patients (P= 0.920), and positive patients for COVID 19 (P= 0.234). The ARB/ACE inhibitor consumption was not associated with the COVID 19 infection (P=0.527, crude OR= 1.407, 95%CI= 0.489- 4.052). Conclusion: Children with a history of previous congenital heart disease surgery are more susceptible to infections; especially those infections with pulmonary involvements, as the lung involvement could cause worsening of the patient’s condition by aggravating pulmonary hypertension. The results of the current study indicate that these patients are more prone to COVID19 infection compared to the healthy children population.